Regional disparities in Gujarat dairy development - Principal component approach - MAHIDA, DARSHNABEN P; SENDHIL, R; SIROHI, SMITA; CHANDEL, B S; PONNUSAMY, K; SANKHALA, GOPAL (The Indian Journal of Animal Sciences, 2018)
Growing regional inequalities is a major concern for policy makers on developmental front. The present study reveals the regional disparities in dairy development of Gujarat which is considered as a role model for dairy industry in India. The relative development of 26 districts in Gujarat was measured by a composite dairy development Index (DDI) using 18 different indicators. Variables related to milk production, availability of resources, infrastructure facilities and dairy cooperatives were considered for the study. Holding linearity relationship assumption, principal component analysis was employed to develop the DDI. As per the index score, Anand, Banaskantha, Mehsana, Sabarkantha, Gandhinagar, Patan and Jamnagar were grouped as highly developed. Kheda, Rajkot, Porbandar, Junagadh, Amreli, Bhavnagar, Kachh, Ahmedabad, Surat and Bharuch were categorized as moderately developed while Dang, Dahod, Narmada, Panchmahal, Surendranagar, Navsari, Vadodara, Tapi and Valsad were placed in low dairy developed districts. The study reveals that the strength of dairy cooperative structure in terms of its functions and bovine breed spread can be accounted as prime factors for regional dairy development disparity. Low developed districts lacked in high quality bovine breeds and poor cooperative structure, which needs policy focus. Elimination of the regional disparities could pave way towards the balanced and sustained growth and development of the dairy sector.